Increased bronchiectasis risk and related risk factors in inflammatory bowel disease: a 10-year Korean national cohort study - Jun Su Lee; Bumhee Yang; Hye Soon Shin; Heajung Lee; Hyun Gyung Chai; Hayoung Choi; Joung-Ho Han; Jai Hoon Yoon; Eung-Gook Kim; Hyun Lee (ERJ Open Research)
Background The association between inflammatory bowel disease (IBD) and an increased risk of bronchiectasis, as well as contributing factors, remains unclear. Additionally, whether bronchiectasis increases disease burden in IBD remains unknown. Therefore, this study aimed to: 1) assess whether IBD increases the risk of incident bronchiectasis; 2) compare the risk of bronchiectasis between individuals with Crohn's disease (CD) and those with ulcerative colitis (UC); 3) identify risk factors for bronchiectasis in individuals with IBD; and 4) examine the disease burden in individuals with IBD and bronchiectasis versus those without. Methods We conducted a population-based matched cohort study involving adults aged ≥20 years with IBD, using data acquired from the Korean National Health Insurance Service-National Sample Cohort database between 2002 and 2012. Results During the mean follow-up of 9.6 years, the incidence rate of bronchiectasis was 419.63 out of 100 000 person-years (PY) and 309.65 out of 100 000 PY in the IBD and matched cohorts (adjusted hazard ratio (aHR) 1.21, 95% CI 1.05–1.39), respectively. UC was associated with increased bronchiectasis risk (aHR 1.42, 95% CI 1.19–1.69), but CD was not. Multivariate Cox regression analyses showed that age, male sex, medical aid, underweight status, COPD and diabetes mellitus were associated with an increased risk of bronchiectasis in the IBD cohort (p<0.05). The mortality, emergency department visit and hospitalisation rates were significantly higher for individuals with IBD and bronchiectasis compared with those without bronchiectasis (p<0.05). Conclusion IBD is associated with increased risk of bronchiectasis, which results in a greater disease burden in individuals with IBD.